Reproductive characteristics of an invasive species Carassius gibelio (Bloch, 1782) in Ataturk Dam Lake, Turkey - Parmaksiz, Arif; Oymak, Seyit Ahmet; Unlu, Erhan; Dogan, Necmettin; Naim, Darlina Md. (Indian Journal of Fisheries, 2018)
In this study, sex composition, spawning period, fecundity and sexual maturity of the gibel carp, Carassius gibelio (Bloch, 1782), an invasive species in the Atatürk Dam Lake, on Euphrates River,Turkey were studied. C. gibelio specimens were analysed from Ataturk Dam Lake and the percentage of the males and females was 45.55% and 55.45% respectively out of the 110 specimens studied, ranging between age groups I -VI. The age at first maturity was three years for both females and males. The diameter of the egg was smallest in September, with a mean of 0.62 mm, while the mean egg diameter in June was greatest, at 1.54 mm. The absolute fecundity ranged from 1054 to 22548. Reproduction of gibel carp in Atatürk Dam Lake in Turkey was characterised by a young age at first maturity and high spawning capacity that would facilitate population expansion in aquatic environments.